Implementation of the muhadhoroh program in training the public speaking competencies of students at the Ibadurrahman Islamic boarding school Payamabar - Syahid Anshar Alhawari; Abd Rahman (Indonesian Journal Education, 2026)
This study aims to analyze the implementation of the muhadhoroh program in developing students’ public speaking competence at the Ibadurrahman Islamic Boarding School in Payamabar, Stabat, Langkat. The muhadhoroh program is a structured activity designed to train students’ communication skills, self-confidence, and readiness to speak in public as future preachers and community leaders. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the pesantren leadership, supervising teachers (ustadz), and students from the MTs and Aliyah levels. The findings reveal that the implementation of the muhadhoroh program is conducted systematically through planning, implementation, and evaluation stages with active involvement of teachers and student administrators. Supporting factors include students’ motivation, exemplary guidance from teachers, and a supportive religious learning environment, while inhibiting factors involve stage fright, limited facilities, and insufficient preparation of speech materials. Overall, the program significantly contributes to improving students’ courage, speech organization, language mastery, and self-confidence in public speaking. The study highlights the importance of structured communication training as part of soft skills development in Islamic boarding schools.